PENGEMBANGAN BAHAN AJAR BERBANTUKAN APLIKASI ANYFLIP PADA MATERI SISTEM KOORDINASI SISWA KELAS XI - Gusmilarni Gusmilarni; Fitrah Al Anshori; Nur Muhajirah Yunus (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the process of developing teaching materials assisted by the Anyflip application and their validity and practicality. This type of research is development research and uses the ADDIE research model (Analysis, Design, Development, Implement, and Evaluation). The research instruments used were validation sheets and student and teacher response sheets. The data analysis techniques used were validation data and practicality data, the results of this study showed that the media expert test data on the product obtained a validity percentage of 79.6% with very good interpretation criteria. , while based on the test results by material expert validators on the product, the percentage of validity is 100% in very good criteria. The results of the teacher's response questionnaire get a practicality percentage of 97.9% with very good criteria, while the results of the tabulation of student responses get a practicality percentage of 70.4% with good criteria. This criterion shows that the development of teaching materials assisted by the Anyflip application is valid and practical.